Mechanism of Long Non-Coding RNAs in Autophagy and Inflammation of Vascular Endothelial Cells: A Review - Li Peng (Molecular Biology & Nanomedicine, 2020)
Increasing researches have highlighted the properties of long non-coding RNAs (lncRNAs) regulating gene transcription, epigenetics, stem cells differentiation and other biological processes. Vascular endothelial cells have been implicated in the process of angiogenesissince they comprise the morphological basis of cardiovascular system. Vascular endothelial cell dysfunction in vascular endothelial cells affects the occurrence and progression of various cardiovascular diseases while secretion of inflammatory factors can induce vascular endothelial cells dysfunction. Autophagy has been widely regarded as an inflammation-related defensive mechanism in cardiovascular diseases. Emergingstudies have addressed the involvement of lncRNAs in vascular endothelial cells. As vascular endothelia cells exert great effects on the cardiovascular system, this review discusses thecorrelations between lncRNAs and vascular endothelia cells with emphasis on regulation of lncRNAs on both autophagy and inflammation in vascular endothelia cells.